Reconstruction of Orbital Exenteration Defects with Cheek Rotation Flaps: Indications, Technique, Complications, Rehabilitation, and Survival - Baum, Sven Holger; Mohr, Christopher (Facial Plastic Surgery, 2021)
The objective of this study was to examine the role of cheek rotation flaps in the reconstruction of orbital defects after exenteration. From January 2000 to August 2018, patients undergoing orbital exenteration and reconstruction with cheek rotation flaps were enrolled in this retrospective study. All patients were evaluated for wound complications, orbital rehabilitation, tumor relapse, and survival. Thirty patients completed the study. Fourteen complications allocated to 11 patients were assessed. The most common complications were seroma (13%), temporary facial nerve weakness (13%), and partial necrosis of the flap (10%). A major complication occurred in a total of two patients (7%), so that surgical correction was necessary. Eleven patients had a relapse; 15 patients died as part of the follow-up. Fifteen patients were treated with facial prostheses. The overall survival rate was 61% after 1 year and 42% after 5 years. Follow-up periods ranged from 6 to 95 months. Cheek rotation flap reconstruction after exenteration is a reliable method with a low rate of major complications. It is indicated when an approach to the parotid gland or the neck region is necessary because of suspected lymph node metastasis and in elderly patients because of their skin's laxity. It can be performed as primary or secondary reconstruction. Good esthetic results can be achieved, especially after endosseous implantation.
Keywords: cheek rotation flap; orbital exenteration; reconstruction; complications; survival